Updated search for the standard model Higgs boson in events with jets and missing transverse energy using the full CDF data set - Collaboration, CDF; Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2013)
We present an updated search for the Higgs boson produced in association with a vector boson in the final state with missing transverse energy and two jets. We use the full CDF data set corresponding to an integrated luminosity of 9.45 fb${}^{-1}$ at a proton-antiproton center-of-mass energy of $\sqrt{s}=1.96$ TeV. New to this analysis is the inclusion of a $b$-jet identification algorithm specifically optimized for $H→ b\bar{b}$ searches. Across the Higgs boson mass range $90 \le m_H \le 150$ GeV$/c^2$, the expected 95% credibility level upper limits on the $V H$ production cross section times the $H→ b\bar{b}$ branching fraction are improved by an average of 14% relative to the previous analysis. At a Higgs boson mass of 125 GeV$/c^2$, the observed (expected) limit is 3.06 (3.33) times the standard model prediction, corresponding to one of the most sensitive searches to date in this final state.